Penyalahgunaan Narkotika dan Obat Obatan Terlarang Perspektif Kriminologi (Studi Kepolisian Resor Pohuwato) (Universitas Islam Balitar, Blitar, 2022)
The abuse of narcotics and illegal drugs in Pohuwato Regency involves the lower class and various ages, which is a local circulation and inter-provincial trade, namely Central Sulawesi, Gorontalo, and North Sulawesi. This study analyzes the factors causing the abuse of narcotics and illegal drugs, as well as the efforts made to prevent and overcome them. To answer the problem used empirical juridical research. The results obtained that the narcotics abuse factor can be seen from the factors of dealers, users, education, and association. Various efforts were made to prevent and overcome it using preventive and preemptive.